The handbook of Electrical Resistivity : new materials and pressure effects - Dyos, G. T. (Institution of Engineering and Technology, 2012)
This book reviews development in the following fields: measurement techniques and material resistivity graphs.
Originally published as: Electrical Resistivity Handbook. London: P. Peregrinus, 1992.
"This book updates and expands the editor's ... Electrical resistivity handbook"--Page 4 of cover.
Keywords: Electric resistance -- Measurement -- Handbooks, manuals, etc.; Electric resistance -- Measurement -- Charts, diagrams, etc.; elektronické knihy; electronic books